Measuring Organizational Performance and The Role of Performance Management Using Profitability Ratio - Setiawati, Eka; Ngamal, Yohanes (Syntax Corporation, 2024)
The purpose of this research is to find out how PT. X applies performance management and performance as a measuring tool. The data collection method in this research is library research. In its implementation, Library Research is carried out by reading, studying and taking notes on various literature or reading materials that are appropriate to the subject matter, then filtered and outlined in a theoretical framework of thought.